Effectiveness of nostalgia marketing in contemporary movies on consumers from young generation. - Kopchenova, Anna; Machek, Martin; Sádlová, Barbora; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis explores the effectiveness of nostalgia marketing in modern movies on the younger generation. The main goal of the research is to understand whether and what impact nostalgia marketing in films has on young people. The foundation of the theoretical framework is based on the use of nostalgia in marketing, its impact on consumer behaviour and the connection between nostalgia and movies. A qualitative approach, including in-depth interviews with Generation Z consumers of Slavic nations and industry experts, constitutes the primary data collection method. The results of the data analysis are presented, discussed, and recommendations to the filmmakers are given. The results of this study indicate that nostalgia marketing in movies is a successful technique for appealing to the younger generation and that it can arouse positive feelings. However, relying only on nostalgia marketing can be harmful. Instead, it is crucial to find a balance between the well-known and the new.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses